Experimental Study on Aspect Ratio and Velocity Intensity of Scour Around Submerged Pile Groups - Lu, Youxiang; Wang, Zhenlu; Yin, Zegao; Du, Shengtao; Pan, Xinying; Liang, Bingchen (Frontiers in Marine Science, 2022)
Submerged pile groups are important components of complex piers in hydraulic engineering and are analogues for a range of subsea structures. These may sustain severe damages from local scour. The velocity intensity (U⁄U_c , the ratio of critical velocity to mean velocity) and aspect ratio (H⁄D_p , the ratio of pile height to pile diameter) are critical variables in this scour process. However, previous studies on scour around submerged pile groups were conducted in clear-water condition (U⁄U_c < 1). In addition, many research studies are being conducted in shallow water flow conditions, which cannot eliminate the effect of the water depth on the scour process. Thus, these research studies cannot directly be applied to live bed scour around submerged structures. To expand the velocity intensity and aspect ratio of scour around submerged pile groups, flume experiments were conducted with uniform quartz sand in both clear-water and live-bed conditions. Pile groups with different heights are adopted as experimental models. An improved time factor for both clear-water and live bed scour around submerged structures is determined with the present experiments to extrapolate the scour depth of the present work to the equilibrium scour depth. This new time factor is then tested with experimental data from literature. The tests demonstrate that this new time factor can reliably predict the scour process and equilibrium scour depth for submerged structures. Empirical relationships to demonstrate the effects of the studied variables including the equilibrium scour depth, scour area, and scour volume are presented. Different methods to predict the effects of the velocity intensity and aspect ratio on the scour depth are compared based on the present work. Furthermore, a correction coefficient is proposed to illustrate the effect of aspect ratio on scour depth. Then, equations of scour area and volume are derived according to the present experiments.